Biomonitoring for pollution assessment: A case study in Kasibeh Reserve in Al-Madain / East of Baghdad (Texas Journal of Agriculture and Biological Sciences, 2023)
In the context of an ecological approach of assessing pollution in Reserve, biomonitoring renders a strategic method for estimating ecosystem health. Rapid bioassessment method using benthic macroinvertebrates as ecological indicators was successfully applied in Kasibeh Reserve in Al-Madain / East of Baghdad, surveyed for a period of three months for recording physicochemical variables of water and estimating the diversity of benthic and biotic indices. The spatial and temporal variability in macroinvertebrate communities and water quality showed noticeable ecological degradation. The taxonomic groups recorded included Oligochaeta, Nematoda, Mollusca and aquatic insects. The pollution index HFBI values ranged from 4.95 to 6.03 indicating very poor water quality conditions in the latter. The percentage EPT taxa and BMWP score showed distinct variation with highest biological monitoring working party score substantiated by the presence of pollution intolerant taxa. The present paper discusses the reasons for ecological degradation of the Kasibeh Reserve in Al-Madain and effectiveness as bioindicators in pollution monitoring studies.